Ethics in Engineering Practice and Research - Whitbeck, Caroline (Cambridge University Press, 2011)
"The first edition of Caroline Whitbeck's Ethics in Engineering Practice and Research focused on the difficult ethical problems engineers encounter in their practice and in research. In many ways, these problems are like design problems: they are complex, often ill defined; resolving them involves an iterative process of analysis and synthesis; and there can be more than one acceptable solution. In the second edition of this text, Dr. Whitbeck goes above and beyond by featuring more real-life problems, stating recent scenarios, and laying the foundation of ethical concepts and reasoning. This book offers a real-world, problem-centered approach to engineering ethics, using a rich collection of open-ended case studies to develop skill in recognizing and addressing ethical issues"--